The Western Stemmed Tradition: Problems and Prospects in Paleoindian Archaeology in the Intermountain West. (2nd January 2020) - Smith, Geoffrey M.; Duke, Daron; Jenkins, Dennis L.; Goebel, Ted; Davis, Loren G.; O'Grady, Patrick; Stueber, Dan; Pratt, Jordan E.; Smith, Heather L.
ABSTRACT: We review some of the current problems and prospects in ongoing Western Stemmed Tradition (WST) studies and highlight recent discoveries at important sites in the Intermountain West. While the region has traditionally not been the focus of peopling of the Americas studies, it has received considerable attention in recent years due to the discovery of WST points and other artifacts in Clovis-aged deposits. Fieldwork at sites in Oregon, Idaho, Nevada, and Utah has produced WST assemblages dated to the terminal Pleistocene and early Holocene and generated new fine-grained datasets capable of addressing longstanding questions about WST technology, chronology, and subsistence. Collectively, these efforts have helped to refocus North American Paleoindian studies on the Intermountain West and the role that it played in the peopling of the Americas.